GEO-3144/8144 Teaching Cruise: Geologically controlled hydrocarbon seepage in Hopendjupet and the wider Barents Sea - Serov, Pavel; Patton, Henry; Mazzini, Adriano; Mattingsdal, Rune; Shephard, Grace; Cooke, Frances Ann; Martins de Aguiar, Victor Cesar; Holm, Villads Dyrved; Alessandrini, Giuliana; Meza Cala, Juan Camilo; Luerssen, Paula (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2022)
The CAGE22-6 cruise on-board R/V Helmer Hanssen hosted UiT´s Arctic Marine Geology and Geophysics (GEO-8144 and GEO-3144) field course for PhD and Master students, and was carried out in collaboration with NPD – the Norwegian Petroleum Directorate and the INTPART project HOTMUD based at Centre for Earth Evolution and Dynamics (CEED) the University of Oslo. The cruise was also a part of the UNESCO Training Through Research program (formerly, The Floating University) and in the framework of this project is also coded as TTR22. The main scientific objectives of the cruise were to investigate: geological controls on fluid-flow dynamics on an uplifted, repeatedly glaciated, and eroded Northern Norwegian Barents Sea shelf and, the fate of the released hydrocarbons in the water column, on the sea surface, and in the atmosphere. The cruise may be known as: CAGE22_6